2001
DOI: 10.1002/jcla.1026
|View full text |Cite
|
Sign up to set email alerts
|

Asian multicenter trials on urinary type IV collagen in patients with diabetic nephropathy

Abstract: To investigate the changes of renal type IV collagen turnover in diabetic nephropathy, urinary type IV collagen was measured by a highly sensitive one-step sandwich enzyme immunoassay (EIA). Urinary samples were obtained from 698 diabetic patients and 191 healthy adults. Among the patients, 264 had urinary albumin levels of less than 29 mg/g.creatine (Cr) (Stage I: normoalbuminuric stage), 169 had microalbuminuria from 30 to 299 mg/g.Cr (Stage II: microalbuminuric stage), 84 patients had macroalbuminuria of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 12 publications
5
33
1
1
Order By: Relevance
“…Therefore, we measured type IV collagen in the urine as a possible sensitive marker of early kidney damage. The baseline value in our diabetic patients was about 6.0 µg/g cr, which was higher than that reported in nondiabetic controls (3.44 0.11 µg/g cr, mean SEM) (21). Unlike albumin and transferrin, urinary type IV collagen excretion was not increased in the control group during the study.…”
Section: Discussioncontrasting
confidence: 65%
“…Therefore, we measured type IV collagen in the urine as a possible sensitive marker of early kidney damage. The baseline value in our diabetic patients was about 6.0 µg/g cr, which was higher than that reported in nondiabetic controls (3.44 0.11 µg/g cr, mean SEM) (21). Unlike albumin and transferrin, urinary type IV collagen excretion was not increased in the control group during the study.…”
Section: Discussioncontrasting
confidence: 65%
“…Type IV collagen is a major structural component of basement membrane and mesangial matrix; and thus an increase in urinary type IV collagen is considered to reflect acceleration of fibrosis in the kidney. It has been reported that the more diabetic nephropathy progresses, the higher the concentration of urinary type IV collagen becomes (48)(49)(50). Moreover, increase in urinary type IV collagen has been shown to be ameliorated by an ACE-I, indicating that ACE-Is have an antifibrotic effect (51).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical situations, serum levels of type IV collagen in liver fibrosis and urine levels of type IV collagen in diabetic nephropathy reportedly correlate with the degree of liver and kidney fibrosis, respectively. 13,14 The serum concentrations of type IV collagen also increased in patients with IPF. 15 However, little is known of the expression and role of type IV collagen, especially in early fibrotic lesions of IIPs.…”
mentioning
confidence: 99%